Pengayaan Pengetahuan Dan Pembiasaan Perilaku Melalui Pendidikan Kesehatan Pada Remaja Di Mojokerto (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Adolescent health is a complex issue. In dealing with this problem, it is often found that teenagers will seek as much information as possible, especially in a time of speedy technological developments like today. The information sought starts from growth and development, health, relationships, fashion trends, etc. The ability to filter the truth from the information obtained needs to be paid attention to. This community service activity aims to enrich knowledge and familiarize teenagers with healthy behaviour in Mojokerto. The method used was health education conducted in 5 high schools/vocational schools in the Mojokerto area with non-communicable diseases, infectious diseases, risky sexual behaviour, stunting incidents, and bullying/bullying. Participants in this activity are students from class X - XII. The results obtained from this community service activity are the increasing knowledge of adolescents about adolescent health, which includes non-communicable diseases, infectious diseases, risky sexual behaviour, stunting incidents, and bullying/bullying. Before the health counselling, most participants had sufficient category knowledge (68,8%); after the health education, almost all participants had good category knowledge (86,7%). Understanding and educating teenagers about health through multisectoral and multidimensional collaboration is essential.
Keywords: health education; knowledge; behavior; adolescent